Integration Of Learning Organization Ideas And Islamic Core Values Principle At University - Aini, Ahmad; Norrihan, Sulan; Anita, Abdul Rani (Emerald Publishing Limited, 2017)

(untitled)
Purpose–The concept of learning organization has been inspiring both public and private sectors since the early 90s. This paper discusses the implementation of learning organization ideas along with the organization’s core values at one of the public universities in Malaysia. The purpose of this paper is to identify the components of core values that support the development and maintenance of learning organization ideas. It also aims to examine the potential integration of the learning organization idea with organizational core values. Design/methodology/approach– The study analyses the application of learning organization principles based on Örtenblad’s (2002) four understandings of learning organization, which are organizational learning, learning at work, learning climate and learning structure, along with the five core values initiatives at the university. Findings– This study suggests that the university core values and the learning organization idea work harmoniously with each other. This paper provides examples of the application of the learning organization idea and the core values attribute and how both fit into each other in one of the Malaysian public universities. A learning organization– core values matrix is proposed at the end of the paper. Research limitations/implications– This research uses the specific case of organizational core values that are established based on Islamic principles. Opportunities for further research can be a study of learning organizations in other core values environment and also from a different belief system. Practical implications– Learning organization is relevant and in harmony with Islamic environment. Originality/value– The paper provides real examples of learning organization practices within the core values agenda in a Malaysian university.